Contralateral nodal failures in oropharyngeal cancers after TORS and unilateral neck management: a retrospective study - Axel Sahovaler; John J. W. Lee; Wei Xu; Susie Su; Ali Hosni; Andrew Bayley; David P. Goldstein; John R. de Almeida (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Report the incidence of contralateral nodal failure rates in well-lateralized oropharyngeal carcinoma treated with upfront surgery and unilateral neck management. Methods Lateralized oropharyngeal carcinomas treated with upfront surgery using transoral robotic surgery (TORS) and unilateral neck management (unilateral neck dissection ± unilateral radiation treatment) were identified. Primary endpoint was contralateral regional control (CRC). Secondary endpoints were local control (LC), and overall survival (OS). Results Thirty-two patients were included. Pathologic T categories included 66% pT1, 31% pT2 and 3% pT3. Nodal diseases comprised 41% N0 and 47% N1 (AJCC 8th). Twenty-three (72%) patients had HPV related tumors. 3-years CRC, LC and OS were 100%, 96% (89–100) and 96% (CI 89–100). One patient developed a second primary with contralateral nodal disease. Only one patient died from another primary cancer. Conclusion In selected patients with lateralized oropharyngeal cancer, treatment with TORS and ipsilateral management of the neck may be oncologically safe without significant risk of contralateral failure. Level of evidence: Level 2. Graphical abstract